Analisis Pengendalian Kualitas Produksi Guna Meminimumkan Jumlah Produk Cacat dengan Metode Statistical Process Control (SPC) pada PT ABC - Aurora Nindi; Idris, Ahmad; Saputra, Beny Mahyudi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
The quality of the final product determines the success of a company, especially in the manufacturing industry. This study aims to analyze the causes of defective products in plywood products, with the hope of minimizing the number of defective products produced, thereby improving product quality. The method used is statistical process control (SPC) by conducting observations and interviews to understand the quality control implemented. The results of the study indicate that the production process at PT ABC is still outside the control limits based on P-Chart calculations, indicating significant deviations. The main factors causing defective products come from human, machine, and raw material aspects. By conducting a thorough evaluation of the production process that is currently outside the quality control limits and focusing on identifying the causes of deviations, appropriate and effective corrective steps can be determined. SOP training and supervision, mentoring programs, routine machine maintenance, appropriate temperature and pressure settings, and periodic measurement of raw material moisture content are expected to help minimize the number of defective products that occur so that product quality is maintained.